A systematic review: dosimetric characteristic of optically stimulated luminecence (osl) dosimeter with photon beam in radiotherapy - Zolkifli, Muhammad Firdaus (2020)
The advancement in radiotherapy techniques impose a challenge for physicist to find the most accurate and precise dosimetry systems to be used in dose measurements especially in quality assurance programs. This paper reviews the important characteristics of Optically Stimulated Luminescence (OSL) dosimetry especially when in use with photon beam in radiotherapy clinical settings. Basic principle on how OSL dosimeter works is also presented and the process that affects the outcome of an OSLD measurements is discussed. The results obtained from the articles reviewed proves that OSL dosimeter has good characteristic to be used as dosimeter involving photon beam. The results demonstrate that the nanoDot OSLD have a good dose measurement at photon beam, a linear dose response at low dose, and have a good reproducibility. The results also indicate that OSL dosimeter has a little dependence on energy. The fading of OSL signal and signal depletion per readout also show good results that indicate the suitability of OSLD to be used in routine clinical measurements. Modern OSLDs system such as nanoDot provide an alternative to other older dosimetry system such as TLD with matching accuracy at better efficiency.